A 6-month-old girl with mesenteric teratoma: A Case report and literature review - Jin, Yuyan; Zhang, Yanan; Chen, Yongwei; Huang, Jinshi (Frontiers in Pediatrics, 2023)
An otherwise healthy 4-month-old girl presented to the community health service center because her abdomen was distended. Over the next 2 months, the girl's abdomen gradually became more distended. Her examination was notable for abdominal distention with a large, mobile, non-tender abdominal mass. Abdominal ultrasound images and subsequently obtained CT images showed a large, circumscribed cystic and solid mass. This led to the presumptive diagnosis of teratoma of the mesentery. The mass was completely resected during a laparotomy. The pathology, along with the surgical findings and imaging, led to the final diagnosis.